2000
DOI: 10.29203/ka.2000.351
|View full text |Cite
|
Sign up to set email alerts
|

Filobasidiella lutea: parasitism of Hypochnicium vellereum

Abstract: The presence of haustoria! branches and a restricted host range suggest that Filobasidiella lutea is a mycoparasite. Microscopic features are illustrated from recent Italian collections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The haustorial branches in Filobsidiella depauperata are morphologically similar to those in F. lutea (see GINNS & BERNICCHIA 2000). In both species the inflated base of the branch arises directly from a hypha and is subtended by a simple septum.…”
Section: Discussionmentioning
confidence: 83%
“…The haustorial branches in Filobsidiella depauperata are morphologically similar to those in F. lutea (see GINNS & BERNICCHIA 2000). In both species the inflated base of the branch arises directly from a hypha and is subtended by a simple septum.…”
Section: Discussionmentioning
confidence: 83%
“…There are only two strains of C. depauperatus available: CBS7841, which was isolated from a dead spider in Canada ( Malloch et al, 1978 ), and CBS7855, which was isolated from a dead caterpillar in the Czech Republic ( Kubátová, 1992 ). Interestingly, C. depauperatus , possibly along with C. luteus , are the only naturally occurring Cryptococcus species with no known yeast phase ( Malloch et al, 1978 ; Kwon-Chung et al, 1995 ; Roberts, 1997 ; Ginns and Bernicchia, 2000 ). Indeed, in contrast to the dimorphic growth of C. neoformans and C. gattii , which are usually yeasts in the asexual stage and produce hyphae, basidia, and basidiospores during the sexual stage, C. depauperatus grows by continuously producing hyphae, basidia, and basidiospores under typical laboratory conditions ( Kwon-Chung et al, 1995 ) with no budding yeast cells observed during its entire life cycle.…”
Section: Introductionmentioning
confidence: 99%